Case Report: Fulminant Celiac Disease With Combination Immune Checkpoint Therapy - Falade, Ayo S.; Reynolds, Kerry L.; Zubiri, Leyre; Deshpande, Vikram; Fintelmann, Florian J.; Dougan, Michael; Mooradian, Meghan J. (Frontiers in Immunology, 2022)
Since the first approval of immune checkpoint inhibitors (ICIs) in 2011, these agents have rapidly become an integral treatment option across tumor types. However, with the increased adoption of ICIs, the incidence of immune-related adverse events (irAEs) continues to rise, and rare toxicity continues to be reported. Here, we present a case of a 70-year-old male patient with widespread metastatic melanoma who developed rapid onset anasarca and transaminitis after initiation of dual anti-PD-1/CTLA-4 inhibition with nivolumab and ipilimumab. An extensive workup was performed with serologies returning positive for anti-tissue transglutaminase immunoglobulin (tTG-IgA) and endoscopy revealing duodenal mucosal atrophy with duodenal biopsies confirming celiac disease. All symptoms resolved after initiation of a gluten-free diet without the addition of immunosuppression. This case highlights the importance of considering celiac disease in patients with suspected protein-losing enteropathy on ICI, the fulminant nature this uncommon irAE can present with, and underscores the broad differential clinicians must maintain when managing presumed irAEs.